Accommodative Multiculturalism: Social Relations of Inqilabi Islamiyah Islamic Boarding School Students in Dampit with Non-Islamic Communities on the Semeru Slopes, Malang - Triyaningsih, Heny; Nugraha, Aat Ruchiat; Anggrayni, Dewi (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2025)
The social situation in the form of a multicultural society is a natural condition that requires healthy social relations in order to minimize clashes and conflicts. Especially if two or more groups from different religions, ethnicities or tribes live in the same area. One of the multicultural realities is the coexistence between the Inqilabi Islamiyah Islamic Boarding School and the majority Buddhist and Christian village population on the Semeru Slopes, Malang. This research aims to examine the form of social relations between Islam, Buddhism and Christianity in maintaining harmonious interactions and classify the types of multiculturalism that occur on the Semeru Slopes. This research uses a qualitative method using documentations and interviews. The study indicated that social relations between Islam and Buddhism on the slopes of Mount Semeru are dominated by interpersonal communication in the form of mutual cooperation. The type of multiculturalism was the accommodative multicultural type, where all religions have equal rights. It can be concluded that Islam-Buddhist relations in the region are relatively harmonious and stable, not built through formal institutions, but rather supported by interpersonal communication practices that arise in simple everyday life, which can foster tolerance and strengthen social cohesion between the santri community and the Buddhist community. This development is characterized by awareness and togetherness in daily interactions between residents, regardless of religious background.